SOCIAL MEDIA ON CONSUMER PURCHASE INTENTION IN SHOPEE MARKETPLACE - Akmal Abdullah; Adrian Febriana Dima; Norvadewi Norvadewi; I Nyoman Tri Sutaguna; Sumarni Sumarni (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine how social media affects consumers' purchase intentions. 181 respondents were given questionnaires as part of a nonprobability sampling strategy that also included a quantitative methodology in this study. The data analysis approach used in this study was multiple linear regression analysis. When using the Likert scale approach of validity, operational variables were measured using SPSS 25.0, a computer measuring tool. The results showed that brand image, social media, electronic word-of-mouth, perceived value, and brand image were all significantly positive predictors of purchase intention. The component in this study that has the most effect on consumers' motivation to purchase is perceived value.